1999
DOI: 10.1016/s0308-5961(98)00076-7
|View full text |Cite
|
Sign up to set email alerts
|

Telecommunications productivity, catch-up and innovation

Abstract: This study examines telecommunications productivity, technological catch-up and innovation in 74 countries for the period 1991-1995. A summary of partial productivity indicators is presented, and total factor productivity (TFP) growth is calculated using the Malmquist productivity change index. Decomposition of the Malmquist index provides preliminary evidence that developing countries can enhance productivity through catch-up. An econometric model is estimated that relates innovation to market size and two me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 11 publications
(5 reference statements)
1
40
0
Order By: Relevance
“…Finally, most African economies were characterized by weak institutions, also subsidized and unprofitable state-owned enterprises which were detrimental to the development of the telecommunication sector [5]. Thus, the African telecommunications industry was comparatively inefficient [2], serving only a small part of the population residing in cities.…”
Section: Overview Of the Telecommunications Development In The Africamentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, most African economies were characterized by weak institutions, also subsidized and unprofitable state-owned enterprises which were detrimental to the development of the telecommunication sector [5]. Thus, the African telecommunications industry was comparatively inefficient [2], serving only a small part of the population residing in cities.…”
Section: Overview Of the Telecommunications Development In The Africamentioning
confidence: 99%
“…As explained in Section 1; both Madden et al [2] and Lam et al [3] had included African countries in their analysis at a global level, however, their results on productivity growth of African countries showed opposite developments. While the former showed that productivity in the African telecommunications industry had declined by 3.7% per annum from 1990 to 1995, the later found that productivity had grown at an annual rate of 6.8% from 1980 and 2006.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, findings in the context of TEs may be better generalized beyond the small group of highly developed countries. This is especially important for the purposes of framework building and validation, for it was previously noted that the insights reporting the overall positive effects of investments in ICT (OECD, 2005a,b,c;IMF, 2001;Samoilenko & Osei-Bryson, 2008a,b) in the context of the relatively homogenous developed countries (Lam & Lam, 2005;Madden & Savage, 1999;Dunne et al, 2004;Siegel, 1997) might not be applicable to a more diverse environment of emerging, developing and transition economies (Roztocki & Weistroffer, 2008;Hoskisson et al, 2000).…”
Section: Investments In Telecoms Represent An Important Subset Of Ovementioning
confidence: 99%